The Road to Recovery #1: Introduction - Cody Gusto; Colby Silvert; John Diaz (EDIS)
This first publication in the Road to Recovery series provides a brief introduction to some core concerns and considerations for Extension professionals as they adapt their outreach, education, and evaluation efforts during a pandemic and recovery. This new 3-page publication of the UF/IFAS Department of Agricultural Education and Communication also includes an overview of the subsequent articles in the Road to Recovery series. Written by Cody Gusto, Colby Silvert, and John Diaz. https://edis.ifas.ufl.edu/wc379